Polymerization of recombinant tau core fragments in vitro and seeding studies in cultured cells - Paterno, Giavanna; Bell, Brach M.; Riley-DiPaolo, Alexis; LaVoie, Matthew J.; Giasson, Benoit I. (Frontiers in Neuroscience, 2023)
The relative polymerization of specific tau protein cores that define Alzheimer's disease, Pick's disease and corticobasal degeneration were investigated using amyloid fluorometry and electron microscopy. In addition, the relative prion-like activities of polymers comprised of these respective tau protein segments were investigated in a cell-based assay. It is demonstrated that the seeding activities of specific tau core fibrils are affected by the presence of pathogenic tau missense mutations and the microtubule binding domain composition of tau. The unique impact of tau phosphorylation on seeding propensity was also investigated by altering stretches of phospho-mimetic and phospho-null residues in the presence of Alzheimer's disease tau core fibrils. These results have important mechanistic implications for mutation and isoform-specific driven pathogenesis.